Synthesis of some tropane-based compounds targeting colon cancer - Samir, Nermin; George, Riham F; Elrazaz, Eman Z; Ayoub, Iriny M; Shalaby, ElSayed M; Plaisier, Jasper R; Demitri, Nicola; Wink, Michael (Future medicinal chemistry, 2020)
Background: In continuation of a previous work concerned with the anticancer activity of some 8-alkyl-2,4-bisarylidene-8-nortropan-3-ones, this work focuses on further modification to the tropane/pyran fused skeleton aiming to obtain improved anticancer activity. Methodology: Reaction of 8-alkyl-2,4-bisarylidene-8-nortropan-3-ones 1-21 with malononitrile under basic conditions afforded tropane/pyran hybrids 22-40 and tropane/pyridine hybrids 41, 42. X-ray crystallography for compounds 22 and 41 as representative examples confirmed their structures. They were tested for their anticancer activity in the HCT116 cell line. Results: Compounds 26 and 33 were the most active compounds with IC50 values of 3.39 and 0.01 μM against HCT116. Moreover, they revealed cyclin-dependent kinase-2 (CDK2) inhibition with IC50 = 104.91 and 49.13 nM, respectively. Furthermore, molecular docking of compounds 26 and 33 in the active site of CDK2 confirmed the obtained results. Conclusion: Tropane/pyran scaffold can be considered as a promising core for anticancer agents acting as CDK2 inhibitors.
Gesehen am 03.02.2021